Gelatin microparticles aggregates as three-dimensional scaffolding system in cartilage engineering - García Cruz, D. M. (2013)
A three-dimensional (3D) scaffolding system for chondrocytes culture has been produced by agglomeration of cells and gelatin microparticles with a mild centrifuging process. The diameter of the microparticles, around 10 μ, was selected to be in the order of magnitude of the chondrocytes. No gel was used to stabilize the construct that maintained consistency just because of cell and extracellular matrix (ECM) adhesion to the substrate. In one series of samples the microparticles were charged with transforming growth factor, TGF-β1. The kinetics of growth factor delivery was assessed. The initial delivery was approximately 48 % of the total amount delivered up to day 14. Chondrocytes that had been previously expanded in monolayer culture, and thus dedifferentiated, adopted in this 3D environment a round morphology, both with presence or absence of growth factor delivery, with production of ECM that intermingles with gelatin particles. The pellet was stable from the first day of culture. Cell viability was assessed by MTS assay, showing higher absorption values in the cell/unloaded gelatin microparticle pellets than in cell pellets up to day 7. Nevertheless the absorption drops in the following culture times. On the contrary the cell viability of cell/TGF-β1 loaded gelatin microparticle pellets was constant during the 21 days of culture. The formation of actin stress fibres in the cytoskeleton and type I collagen expression was significantly reduced in both cell/gelatin microparticle pellets (with and without TGF-β1) with respect to cell pellet controls. Total type II collagen and sulphated glycosaminoglycans quantification show an enhancement of the production of ECM when TGF-β1 is delivered, as expected because this growth factor stimulate the chondrocyte proliferation and improve the functionality of the tissue.